2016
DOI: 10.1002/fee.1310
|View full text |Cite
|
Sign up to set email alerts
|

Captive pandas are at risk from environmental toxins

Abstract: Ex situ conservation efforts are the last resort for many critically endangered species, and captive breeding centers are thought to provide a safe environment for producing individuals for eventual re-introduction to the wild. The giant panda (Ailuropoda melanoleuca) is one of the world's most endangered animals and is a widely recognized symbol for conservation. Here, we report that captive pandas in China experience environmental and dietary exposures to high concentrations of persistent organic pollutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…, Chen et al. ). Samples from atmospheric deposition were freeze dried before being spiked with 13 C‐labeled surrogate standards (Environmental Protection Agency [EPA] methods 1613B and 1668A) and undergoing accelerated solvent extraction with dichloromethane: hexane (1:1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Chen et al. ). Samples from atmospheric deposition were freeze dried before being spiked with 13 C‐labeled surrogate standards (Environmental Protection Agency [EPA] methods 1613B and 1668A) and undergoing accelerated solvent extraction with dichloromethane: hexane (1:1).…”
Section: Methodsmentioning
confidence: 99%
“…Captive pandas at SWARC and wild pandas elsewhere in the region are exposed to heavy metals and persistent organic pollutants (POPs), including PCBs (polychlorinated biphenyls), PCDDs (polychlorinated dibenzo‐p‐dioxins), and PCDFs (polychlorinated dibenzofurans) through their diet of bamboo (Chen et al. ). However, the ultimate origin of these pollutants is not known.…”
Section: Introductionmentioning
confidence: 99%
“…com/link") (pink area in Figure 2 With rapid industrialization, environmental pollution is increasing and following a similar trajectory to that previously seen in developed countries (Seinfeld 2004). Recent studies also have revealed that captive pandas are exposed to high concentrations of toxic chemicals, including PCDDs (polychlorinated didenzo-p-dioxins), PCDFs (polychlorinated dibenzofurans), PCBs (polychlorinated biphenyls), PBDE (polybrominated diphenyl ethers), and heavy metals (Chen et al 2016;Chen et al 2017a;Chen et al 2017b;Chen et al, forthcoming). A detailed study of the Qinling subspecies demonstrated that exposure to Figure 2.…”
Section: Captive Panda Populations Face Their Own Risksmentioning
confidence: 99%
“…Since 1978, 13 conservation zones have been established in the Qinling Mountains to protect the giant panda, and the largest density area of pandas is the Foping Nature Reserve that belongs to Xinglongling population habitat. However, a recent study had found that pandas in the Foping Nature Reserve were exposed to toxic metals via their food, the bamboo species Fargesia qinlingensis and Bashania fargesii, and soil in their core activity area (Chen et al 2016). In order to comprehensively explore the ecological risk of metals in Qinling giant panda habitat and the giant pandas' exposure levels to toxic metals and health risk, soil, water, bamboo, and feces samples were collected in independent distribution areas of six Qinling giant panda populations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bamboo (Fargesia dura) growing in a mining area accumulated Cd, Cu, Pb, and Zn with concentrations of Cd and Zn being greater in bamboo tissue than in the soil (Yanqun et al 2004), and likewise, bamboo (Fargesia qinlingensis and Bashania fargesii) have higher concentrations of Cd and Pb in the Foping Nature Reserve that is one of the core activity areas of Qinling giant panda (Chen et al 2016). Pandas can consume an average 30 kg of bamboo shoots and leaves per day (Tuanmu et al 2013).…”
Section: Introductionmentioning
confidence: 99%